2015
DOI: 10.1007/s10552-015-0676-3
|View full text |Cite
|
Sign up to set email alerts
|

Prior human polyomavirus and papillomavirus infection and incident lung cancer: a nested case–control study

Abstract: Purpose To test whether infection with select human polyomaviruses (HPyV) and human papillomaviruses (HPV) is associated with incident lung cancer. Methods We performed a nested case-control study, testing serum from the Carotene and Retinol Efficacy Trial (CARET), conducted 1985–2005, for antibodies to Merkel cell (MCV), KI (KIV), and WU (WUV) HPyVs as well as to six high-risk and two low-risk HPV types. Incident lung cancer cases (n=200) were frequency-matched with controls (n=200) on age, enrollment and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
(66 reference statements)
2
10
0
Order By: Relevance
“…While studies targeting at the direct relationship between lung cancer and lung microbiome are quite limited at present, there have been interesting studies documenting persistent lung infections and inflammation can favor carcinogenesis . And certain types of microbial agents or products may positively or negatively modulate lung cancer development and/or progression .…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…While studies targeting at the direct relationship between lung cancer and lung microbiome are quite limited at present, there have been interesting studies documenting persistent lung infections and inflammation can favor carcinogenesis . And certain types of microbial agents or products may positively or negatively modulate lung cancer development and/or progression .…”
Section: Introductionsupporting
confidence: 56%
“…While studies targeting at the direct relationship between lung cancer and lung microbiome are quite limited at present, there have been interesting studies documenting persistent lung infections and inflammation can favor carcinogenesis. [25][26][27][28][29][30][31][32] And certain types of microbial agents or products may positively or negatively modulate lung cancer development and/or progression. 27,30,32,33 A large epidemiological study in humans suggested that the frequency of lung cancer increases upon use of repeated courses of antibiotics providing circumstantial evidence that some links may exist between the bacterial microbiota and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In this seroepidemiologic study of the association of HPyV and HPV and incident lung cancer in Asia, multivariable regression analyses of pooled histology types and visual exploration of boxplots stratified by histology type demonstrated no evidence of an association between the levels of these viral antibodies and lung cancer. These results are consistent with our previous seroepidemiologic study in an American population, which also found no association between HPyV antibody levels and lung cancer [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite prior infection with human polyomaviruses being nearly ubiquitous [ 19 ], prior studies report that high levels of MCV antibodies were associated with Merkel cell carcinoma [ 20 ]. However, in the only other seroepidemiologic study, antibodies to MCV, KIV and WUV were not associated with lung cancer in a US population [ 21 ]. Nevertheless, given the influence of host genetics on susceptibility to cancer, these associations may differ in different populations.…”
Section: Introductionmentioning
confidence: 99%
“…The association between seropositivity for KIPyV and for WUPyV and lung cancer was studied previously, antibodies against VP1 (viral protein 1) and small tumour antigen were detected and analysed. Colombara et al [31, 32] found that previous infections with these polyomaviruses were not associated with lung cancer. The DNA prevalence of KIPyV and WUPyV was studied in different cancer types [9, 11-13, 33-39], but only KIPyV was detected in lung carcinomas [11] and in benign skin tumours [35].…”
Section: Introductionmentioning
confidence: 99%